Analysis of the Validity and Legal Implications of Siri Marriage on the Rights of Wives and Children - Kafka Nafisa Firman; Adyan Dhio Akhdany; Rizky Syahrul Ramadhan (Lembaga Yasin AlSys, 2026)
This study examines the legal dualism of nikah siri (unregistered Islamic marriages) in Indonesia, in which unions are considered valid under sharia by fulfilling pillars such as ijab qabul, wali, witnesses, and mahr, but lack state recognition due to non-registration as mandated by Law No. 1/1974 on Marriage and the Kompilasi Hukum Islam (KHI). Drawing from Qur’anic principles (e.g., Al-Baqarah 2:30; Ar-Rum 30:21) and the context of national pluralism, the study highlights the vulnerability of wives and children who are frequently denied inheritance, maintenance, birth certificates, and broader social protection, as reflected in 28,000 detected cases during 2020–2023 that resulted in approximately 1.5 million unregistered children. Employing a qualitative descriptive case study design, the research uses primary data obtained through in-depth semi-structured interviews with ustaz officiants and triangulates these findings with secondary sources, including fiqh texts, legislation, and prior empirical studies. The findings reveal recurrent sharia defects, such as the absence of a guardian of nasab and unqualified witnesses that render some unions religiously invalid and inclined toward adultery, while deficiencies in state regulation and implementation further entrench gender discrimination and child poverty. Constitutional Court Decision No. 46/PUU-VIII/2010 provides a legal avenue to establish civil ties through evidentiary proceedings, yet marriage isbat (court validation) functions primarily as a remedial mechanism for unions formed before 2015. The analysis underscores persistent tensions between religious legitimacy and civil certainty and concludes that harmonizing maqasid sharia with national law through streamlined digital registration at the Office of Religious Affairs (KUA), retrospective isbat campaigns, and strengthened fiqh education is essential to safeguarding family stability and promoting sakinah mawaddah warahmah.